Level Analysıs of the Relatıonshıp Between Inflatıon, Exchange Rate, Cbrt and Fed Interest Rates of Turkısh Foreıgn Trade - AYTÜRE, Selma; KESKİN, Meltem (Journal of Ecohumanism, 2024)
Foreign trade has become one of the important elements of the financial structure of countries. Money transfer mechanisms have the power to determine the direction of trade in the world. In the study; Türkiye’s exports acording to the country groups were used. In the period 2013:1-2023:11; Panel cointegration, Autoregressive Distributed Lag (ARDL) and Granger causality analyses were used to determine the relationship levels between the Central Bank of the Republic of Türkiye (CBRT), Federal Reserve System (FED) interest rates, Wholesale Price Index (WPI), Consumer Price Index (CPI) and Türkiye’s foreign trade. has been used. As a result of the study; Findings have been obtained that Turkish exports are not affected by the CBRT interest rate decisions and WPI in the short or long term. While the increase in FED interest rates causes a decrease in all of Türkiye’s exports in the long term, it reduces exports to the Turkic Republics, OECD, EFTA, BSEC, CIS, OIC and D8G in the short term. It has been concluded that while there is a unidirectional causality relationship between the CBRT and FED interest rates, WPI and CPI and Türkiye’s exports, there is a bidirectional causality relationship between the exchange rate and Türkiye’s exports.